The Golden Ratio in The Quran (Zien Journal of Social Sciences and Humanities, 2022)
The article on Abjad analyzes the full text of the Quran. It has been shown that the alteration of the text of the Quran by people is protected by Allah and that His main parameters depend on the divine golden ratio